The Effect Of Tax Planning, Leverage and Corporate Social Responsibility on Earnings Management - Billah Safarina; Dyah Ratnawati (Al-Buhuts, 2025)
Earnings management remains a critical issue in financial reporting as it may impair the quality of accounting information and potentially mislead stakeholders in making economic decisions. This study aims to examine the effects of tax planning, leverage, and corporate social responsibility (CSR) on earnings management in manufacturing companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX). The study employs a quantitative research approach using secondary data obtained from companies’ annual reports and financial statements for the period 2019–2022. The sample consists of 19 companies selected through a purposive sampling technique, resulting in 76 firm-year observations. Data were analyzed using multiple linear regression based on the Ordinary Least Squares (OLS) method with the assistance of IBM SPSS version 26. The findings reveal that tax planning and leverage have a significant effect on earnings management, whereas corporate social responsibility does not significantly influence earnings management. These results support Agency Theory, suggesting that managers may utilize tax planning strategies and debt structures as mechanisms to influence reported earnings. This study contributes to the growing body of literature on earnings management within the Indonesian food and beverage industry and provides practical implications for investors and corporate managers in assessing the quality and reliability of financial reporting